CRYOSURGERY IN THE TREATMENT OF NON-MELANOMA SKIN CANCER OF THE EYELID AND PERIOCULAR AREA - RETROSPECTIVE ANALYSIS OF 78 CASES - Tavares, Ermelindo; Gonçalves, J. C. Almeida; Aranha, João (Journal of the Portuguese Society of Dermatology and Venereology, 2013)
Introduction: Cryosurgery is a safe and effective treatment modality for non-melanoma skin cancers of the eyelids and periocular area, with a reported 5-year overall cure rate above 95%. Aim: Retrospective characterization of patients with non-melanoma skin cancer of eyelids and periocular regions diagnosed and treated with cryosurgery at our Department, between 1988 and 2004. Material and Methods: Review of the clinical records and statistical analysis of the following variables: age, sex, occupation, skin type, tumour characteristics, treatment modalities, aesthetic and functional outcomes and follow-up. Results: We treated 78 primary malignant neoplasms, in 78 Caucasian patients, 30 men and 48 women with a mean age of 75.5 years. Seventy-six of the seventy-eight tumours (97.4%) were nodular basal cell carcinoma (BCCs) and two were (2.6%) squamous cell carcinomas. More than half of the tumours were loca- ted in the inner canthus. Fractional cryosurgery was used in 52 cases (66.7%), conventional cryosurgery in 17 (21.8%) and segmental cryosurgery in nine (11.5%). The mean follow-up was 5 years with two relapses observed. There were no functional complications and the cosmetic results were excellent. The overall cure rate was of 97.4%. Conclusions: Fractional cryosurgery was the most used procedure. We achieved excellent functional and aesthetic results and a 97% five-year cure rate. KEYWORDS – Eyelid neoplasms; Cryosurgery; Carcinoma, Basal cell; Carcinoma, Squamous cell; Skin neoplasms.